FIRST RECORD OF THE LESSER MOUSE-TAILED BAT Rhinopoma hardwickii (RHINOPOMATIDAE: CHIROPTERA) FROM SOUTHERN PUNJAB, PAKISTAN - A. Javid; M. Mahmood-ul-Hassan; M. S. Nadeem; N. Rana; N. Khan (Journal of Animal and Plant Sciences, 2012)
The lesser mouse-tailed bat Rhinopoma hardwickii Gray, 1831 has not been recorded from Pakistan except from northern Punjab (Rohtas) and southern Sindh (Karachi, Landhi and Karchat Hills near Hyderabad). These records date back to 1927. Here after 84 years, we provide an account of the third country and first record of this species from southern Punjab. Rhinopomatid bats (n =5) were captured from this region of which two were euthanized to describe their external body, cranial and bacular measurements. This paper compares various morphometeric measurements of these bats to those already mentioned in literatures and documents habitat and new distribution map of this species in Pakistan.
Keywords: Bacula; Cellar; Forearm length; Noor Mahal; Skull; Bahawalpur.